Dolore addominale e vomito per dissecazione dell’arteria vertebrale: un case report di stroke chameleon. - Sara Giannoni; Mariella Baldini; Maria Letizia Bartolozzi; Elisabetta Bertini; Ilaria Di Donato; Serena Colon; Elisa Grifoni; Elisa Madonia; Ira Signorini; Massimo Armellani; Andrea Pierfederico Sampieri; Luca Masotti; et al. (Journal of Biomedical Practitioners, 2025)
INTRODUZIONE